Teknik Pengambilan Keputusan pada Pemilihan Supplier : A Literature Review - Titi Indarwati (Universitas Mercu Buana, 2020)
The presence of the internet and the development of technology make information exchange faster so that consumer preferences for products quickly change. This has an impact on increasingly shorter product life cycles. The company needs to improve the efficiency of supply chain performance in order to have competitive competitiveness. Supplier selection is one of the important activities in the purchasing process and has an impact on the design strategy of supply chain design. This research presents a literature review of supplier selection decision making methods for single sourcing and multiple sourcing cases by collecting articles from relevant international journals from 2010 to early 2020 to find research recommendations for supplier selection in the future. From the results of literature studies that have been carried out, it is necessary to develop a decision-making method that combines qualitative and quantitative criteria to select potential suppliers. The process of selecting suppliers that not only ranks but also determines cut-offs to distinguish which are included in the category of potential suppliers and which are not.